O discernimento da consciência no magistério do Papa Francisco. uma reflexão ético-teológica para a integração de todas e todos - Santos, Carolina Mureb (2024)
Discernment is one of the key themes of Pope Francis's pontificate, frequently mentioned in documents, speeches and messages and was the theme of a cycle of catechesis on wednesdays. Considered by the Christian tradition a spiritual exercise for decision-making guided by the Spirit, discernment is seen by Pope Francis as essential in the journey of Christians. The research presented here aims to analyze the understanding of discernment that emerges from Pope Francis's teaching, as it considers that he presents ethical-pastoral characteristics that contribute to a renewal in the mission of the Church, especially among people in situations considered vulnerable and/or irregular. Therefore, it seeks to rescue and deepen the biblical-theological conception of discernment and other categories that enrich its understanding based on the teaching of the current Pope, such as pastoral kindness and the conception of the human person. Then, from the analysis of some pontifical documents, it intends to identify the theological references of Pope Francis's conception of discernment. Finally, the aim is to propose some ethical and pastoral implications of the practice of discernment for the accompanying and integration of human weaknesses and their contradictions, as well as indicating some themes in which Pope Francis's practice needs to advance